Tingkat Produktivitas Ternak Usaha Sapi Potong Program Kredit Ternak Sejahtera (KTS) di Kabupaten Berau Kalimantan Timur - Hairudin; Sri Hartini (Jurnal Sains dan Teknologi Peternakan, 2020)
This study aims to determine the livestock productivity level of beef cattle business at Prosperous Livestock Credit (PLC) program in Berau regency, East Kaliamntan. This study implemented in Berau regency in three districts namely Teluk Bayur, Sambaliung and Gunung Tabur, with used survey method at PLC program in Berau regency. Data analysis used descriptive analysis by means and standard deviation. The results showed an increase of the beef cattle population in the PLC program by 48.67 %/year from the initial number of beef cattle. Productivity indicated with Pubertas 2.26±0.40 years, S/C 1.35±0.61, Pregnancy Rate 283.53±1.33 days, Age at First Calving 3.04±0.40 years, Calving Rate 81 % with female population, Fertility 65 %, Mortality 8 % with total population, Oestrus Pospartum 40-60 days, Calving interval 12.4±0.44 months. The average of beef cattle business in the PLC program was 10.23 AU/farmer.